Bismuth Nanoparticles Embedded in Carbon Spheres as Anode Materials for Sodium/Lithium‐Ion Batteries. Issue 7 (12th January 2016) - Yang, Fuhua; Yu, Fan; Zhang, Zhian; Zhang, Kai; Lai, Yanqing; Li, Jie
Abstract: Sodium‐ion batteries (SIBs) are regarded as an attractive alternative to lithium‐ion batteries (LIBs) for large‐scale commercial applications, because of the abundant terrestrial reserves of sodium. Exporting suitable anode materials is the key to the development of SIBs and LIBs. In this contribution, we report on the fabrication of Bi@C microspheres using aerosol spray pyrolysis technique. When used as SIBs anode materials, the Bi@C microsphere delivered a high capacity of 123.5 mAh g −1 after 100 cycles at 100 mA g −1 . The rate performance is also impressive (specific capacities of 299, 252, 192, 141, and 90 mAh g −1 are obtained under current densities of 0.1, 0.2, 0.5, 1, and 2 A g −1, respectively). Furthermore, the Bi@C microsphere also proved to be suitable LIB anode materials. The excellent electrochemical performance for both SIBs and LIBs can attributed to the Bi@C microsphere structure with Bi nanoparticles uniformly dispersed in carbon spheres. Abstract : Spheres within spheres : The successful preparation of Bi@C microsphere structures is reported with Bi nanoparticles uniformly dispersed in carbon spheres by aerosol spray pyrolysis technique (see figure). The nanosized Bi particles provide high specific capacity, and the carbon matrix enhances the conductivity and buffers the volume change of the electrode during the cycling. The as‐prepared Bi@C composites also delivered a high specific capacity and showed an excellent rate performance as anode materials for sodium/lithium‐ion batteries.